In vitro evaluation of a novel self-adhesive composite primer modified with nano zinc oxide and hydroxyapatite: antibacterial activity, marginal microleakage, and interfacial elemental analysis - Raghda Kamh; Alshaymaa Abdelmonaem Mohammed; Hamdy Mahmoud Badreldin; Esraa Abdel Ghaffar El Gezawy (BMC Oral Health, 2026)
Abstract Background This study aimed to investigate the antibacterial effects of a self-adhesive 10-MDP contained Primer (Stela primer) modified with nano-sized zinc oxide (ZnO) and hydroxyapatite (HA) particles. Furthermore, it evaluated the extent of marginal microleakage in Class II restorations and conducted elemental analysis of the tooth–primer interface using energy-dispersive X-ray spectroscopy (EDX). Materials and methods The sixty-three premolars enrolled in this study were subjected to class II cavity preparation and divided into three groups according to the primer used (modified Stela primer containing zinc oxide nanoparticles (ZnO-NPs), hydroxyapatite nanoparticles (HA-NPs), and Stela primer without modification). Stela self-adhesive resin composite was applied to all teeth. The teeth were subjected to a microleakage test ( n = 21) for each group and elemental analysis of the tooth–primer interface using EDX ( n = 3) for each group. All modified and non-modified primers were evaluated for their antibacterial activity against Streptococcus mutans (S. mutans). Results No statistically significant differences in marginal microleakage were observed between the modified and unmodified groups at either the occlusal or gingival margins ( P = 0.34 gingivally; P = 0.15 occlusally). EDX analysis showed a notable increase in calcium and phosphorus deposition at the tooth–primer interface in both nanoparticle-modified groups, especially in the HA-NP group, indicating interfacial mineralization ( P < 0.001). The unmodified primer showed no significant changes in mineral content. Adding ZnO-NPs and HA-NPs to the Stela primer greatly improved its antibacterial effect against Streptococcus mutans , with HA-NPs producing the largest inhibition zone. Conclusions Incorporating ZnO-NPs and HA-NPs into Stela primer enhances its biological potential; however, they did not significantly alter the sealing ability (microleakage) compared to the control. Both nanoparticle-modified primers exhibited potent and comparable bactericidal activity against Streptococcus mutans . At the same time, nano-hydroxyapatite demonstrated the most pronounced antibacterial effect and the most significant improvement in mineral deposition at the tooth–primer interface.